Regeneration of the Fibula with Unidirectional Porous Hydroxyapatite - Koji Demiya; Toshiyuki Kunisada; Eiji Nakata; Joe Hasei; Toshifumi Ozaki (Case Reports in Orthopedics)
A fibula graft is one of the most common orthopedic procedures for reconstruction of a bone defect, and some complications related to persistent defects of the fibula have been reported previously. We believe that regeneration of the fibula may be critical for postoperative function and prevention of complications. This report describes a 9-year-old female with Ewing sarcoma of the pelvis who was treated with the double-barrel fibula grafts for pelvic bone defect following tumor resection. The defect after fibular resection was filled with unidirectional porous hydroxyapatite (UDPHAp) implants. A plain radiograph revealed new bone formation and a callus-like structure at one month after surgery and bony union between each UDPHAp implant 5 months after surgery. Resorption of implanted UDPHAp was identified, and partial remodeling of the bone marrow cavity could be seen 1 year 2 months after surgery. A radiograph at final follow-up (5 years 10 months after surgery) demonstrated almost complete absorption of the implanted UDPHAp and clear formation of the cortex and bone marrow in the resected part of the fibula. The patient is able to walk well without any walking supports and to take part in sports activities.